2004
DOI: 10.1111/j.1463-1318.2004.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery: clinical and functional results

Abstract: TEM is a safe procedure, having a low recurrence rate and an acceptable functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 31 publications
5
48
1
1
Order By: Relevance
“…Various published studies have shown a shorter length of hospitalisation in patients undergoing TEM, with an average in patient stay of around 5 days (range 3–8.2) [5, 9, 18,23,24,25, 28,30,31,32,33,34,35,36,37]. This compares favourably with 14.5 days quoted for open procedures [25].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Various published studies have shown a shorter length of hospitalisation in patients undergoing TEM, with an average in patient stay of around 5 days (range 3–8.2) [5, 9, 18,23,24,25, 28,30,31,32,33,34,35,36,37]. This compares favourably with 14.5 days quoted for open procedures [25].…”
Section: Resultssupporting
confidence: 64%
“…Several published reports have consistently demonstrated these benefits [5, 9, 18,23,24,25,26,27,28,29,30,31,32,33], which hold true for both the older and the younger patients.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In their study, patients with a tumour in the distal 7 cm of the rectum had a significant improvement in FISI score (16 v. 5, p = 0.01). Dafnis and colleagues 21 found that patients who experienced post-TEM incontinence had longer surgery durations (175 v. 117 min, p = 0.002). Similarly, Kennedy and colleagues 22 described a correlation between duration of surgery and functional results.…”
Section: Researchmentioning
confidence: 99%
“…Dentre esses resultados, vem ganhando destaque a avaliação da função esfincteriana após a TEM 9,10,11,12,14 . Foi verificada alteração da função esfincteriana clinicamente significativa em 14,7% dos pacientes após a operação.…”
Section: Discussionunclassified